2020
DOI: 10.1371/journal.pone.0238897
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced miR-92a regulates p53 signaling pathway and apoptosis by targeting calcium-sensing receptor in genetically improved farmed tilapia (Oreochromis niloticus)

Abstract: miR-92a miRNAs are immune molecules that regulate apoptosis (programmed cell death) during the immune response. Apoptosis helps to maintain the dynamic balance in tissues of fish under hypoxia stress. The aim of this study was to explore the role and potential mechanisms of miR-92a in the liver of tilapia under hypoxia stress. We first confirmed that CaSR (encoding a calcium-sensing receptor) is a target gene of miR-92a in genetically improved farmed tilapia (GIFT) using luciferase reporter gene assays. In GIF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The main mediator of the biological function of hypoxia, HIF-1α, is a chief controller of oxygen homeostasis and can regulate multifarious cellular functions, such as cell proliferation, apoptosis, and A metastasis (23)(24)(25). A previous study also demonstrated that under hypoxic conditions, the enhancement in HIF-1α expression triggers hypoxia-mediated apoptosis by influencing the expression of downstream molecules (26). Hypoxia was also found to induce cancer metastasis by upregulated HIF-1α expression via promotion of EMT (27).…”
Section: Discussionmentioning
confidence: 99%
“…The main mediator of the biological function of hypoxia, HIF-1α, is a chief controller of oxygen homeostasis and can regulate multifarious cellular functions, such as cell proliferation, apoptosis, and A metastasis (23)(24)(25). A previous study also demonstrated that under hypoxic conditions, the enhancement in HIF-1α expression triggers hypoxia-mediated apoptosis by influencing the expression of downstream molecules (26). Hypoxia was also found to induce cancer metastasis by upregulated HIF-1α expression via promotion of EMT (27).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is mediated by the modulation of the activity of macrophages and dendritic cells, the suppression of liver-resident NK cells, and the induction of TGF-β expression [ 115 ]. Additionally, in 2020, miRNA92a (regulated by hypoxia through HIF1α) [ 116 ] was reported to be released by BMDCs recruited to the premetastatic niche in response to hypoxia. Once secreted, miRNA92a acts by inhibiting its target SMAD7, leading to increased TGFβ secretion by hepatic stellate cells.…”
Section: Hypoxic Secretomementioning
confidence: 99%
“…Furthermore, MiR-92a is a widely studied microRNA, in particular, its role in in ammatory and cancer diseases. Several studies have shown that miR-92 promote the expression of numerous cancer genes and is involved in multiple classical cancerassociated pathways (16)(17)(18)(19)(20)(21)(22)(23)(24). MiR-92a promotes hepatocellular carcinoma cell proliferation and invasion by Recombinant Forehead Box Protein A2 (FOXA2) targeting (25).…”
Section: Introductionmentioning
confidence: 99%